2002
DOI: 10.1046/j.1365-3156.2002.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cervical cancer screening in a poor area: results of a population‐based survey in Rivas, Nicaragua

Abstract: Summaryobjective To obtain baseline information for designing a community-based intervention programme aimed at increasing the cervical cancer screening coverage of women most at risk.methods A population-based survey, using proportional stratified two-stage cluster sampling in Rivas, one of the 16 Departments of Nicaragua. The individuals selected were interviewed at home by one of 26 interviewers, using a structured questionnaire. The questionnaire was designed to elicit (1) knowledge, attitudes and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 15 publications
5
38
1
4
Order By: Relevance
“…Also, all the students had tertiary level of education. The low level of knowledge is similar to findings in developing countries [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…Also, all the students had tertiary level of education. The low level of knowledge is similar to findings in developing countries [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…The remaining 1,857 women (42.8%) were grouped as having adequate screening. In univariable analysis, we compared the characteristic features of women with adequate and inadequate screening and found factors significantly younger age was also a significant factor associated with inadequate screening (Claeys et al, 2002;Thanapprapasr et al, 2012). For women who had low income, they may focus on economical issues than to maintain healthy Loss data : adequate group = 10 (0.5%) and inadequate group = 5 (0.2%) associated with inadequate screening were: aged <45 years, pre-menopause, family monthly income <625 USD, no sexual intercourse, nulliparous, no knowledge about cervical cancer screening, unawareness and poor attitudes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Reports from suburb area of Thailand found 33% or 35% of 'never had' screening (Kritpetcharat et al, 2003;Wongwatcharanukul et al, 2014). In capital cities of other countries, the rates of 'no screening' varied widely from 15-90% (Claeys et al, 2002;Al Sairafi and Mohamed, 2009;Baskaran et al, 2013;Núñez-Troconis et al, 2013;Cunningham et al, 2015). Aside from the 35% of 'never had' screening, 18% and 4% of Bangkok women had only one test or the last test was more than 5 years, making up 57% of the inadequate screening in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that knowledge regarding cervical cancer prevention may be sufficient motivation for many women to undergo screening, regardless of a thorough understanding of the screening process. Fear was the most common barrier to cervical cancer screening 3,[11][12][13] . Agurto, et al found that women believed it was better not to know death was coming than to know it was coming and not be able to do anything about it 14 .…”
mentioning
confidence: 99%